Safety, Efficacy, and Predictors for Late Reintervention After Embolization of Renal Angiomyolipomas – Embolization renal angiomyolipoma - Claesen, Evelien; Bonne, Lawrence; Laenen, Annouschka; Bammens, Bert; Albersen, Maarten; De Wever, Liesbeth; Maleux, Geert (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
Purpose To retrospectively analyze the procedural and long-term clinical outcome of the selective embolization of renal angiomyolipoma. In addition, potential predictive factors for higher risk of late re-intervention were analyzed.Methods Retrospective monocentric study, including 34 consecutive patients, analyzing the safety, efficiency, and long-term clinical outcome of catheter-directed embolization of renal AML. Additionally, the difference in postembolization renal function between patients embolized in the acute and in the elective setting was analyzed. Secondly, we also evaluated whether volume/diameter of the AML and presence of intralesional aneurysms are risk factors for late re-intervention.Results Embolization of renal AML was performed to control volume (n = 21; 62 %) or to stop spontaneous hemorrhage (n = 13; 38 %) with angiographic success in all cases but was associated with renal abscess (n = 1) and pulmonary embolism (n = 1) without a significant difference in renal function before and after embolization (P = 0.513). Volume/diameter (P = 0.276/P = 0.21) and presence of aneurysms before embolization (P = 0.37) are not predictive for a higher risk of late re-intervention.Conclusion Catheter-directed embolization is a safe and effective treatment modality for asymptomatic and bleeding renal AML, without a negative impact on renal function. Initial mass volume/diameter or presence/absence of intralesional aneurysms does not seem to be predictive for late re-intervention.Key Points:Citation Format
Keywords: angiomyolipoma; embolization; complication; predictor clinical success; long-term outcome